Political Economy in International Trade: New Trade Tariff Issues Lead to Mass Layoffs at Textile Companies in the Cikarang Industrial Area: Perspectives and Solutions - Ismuni, Mutdi; Taryanto, Taryanto; Irawan, Pristanto Ria; Rustomo, Rustomo (Dinasti Publisher, 2025)
The rise in Donald Trump's new trade tariffs, which have been imposed in several nations, including Indonesia, is what spurred this study. Reduced output and challenges for clothing and textile businesses exporting overseas, particularly to the US and Europe in general, are the results of this worry. This has led to widespread layoffs, with the most labour - intensive businesses being those in the apparel and textile industries. Examining the political economy of global commerce and the problem of new trade tariffs that have led to widespread unemployment in textile enterprises in the Cikarang Industrial Area are the goals of this study. Regarding the problem of new US trade tariffs, opinions and remedies might be expressed. This research methodology employs a descriptive qualitative approach that focuses on thoroughly describing and then understanding the occurrences that take place. Utilising focus groups, in-depth interviews, document analysis, and observational methods. With a sample of 100 respondents, the population consists of clothing and textile manufacturing and exporting businesses located in the Cikarang Industrial Area. Purposive sampling Data reduction, presentation, conclusion drawing, and result verification were the three steps of the interactive, continuous data analysis that was carried out based on specific criteria in two production businesses and three exporters. According to the findings, businesses voiced their worries about the increased trade tariffs and thought about taking action to reduce them. Hiring Costs of labour and raw materials. Stakeholders think that if this keeps happening, it will make it more difficult to hire new employees. One major effect is that businesses will use mass layoffs. The national government's option is for relevant parties to take proactive, long-term measures.